Empowering Communities, Beyond Energy Scarcity BIWAES 2021 Biennial International Workshop Advances in Energy Studies - Ulgiati, Sergio; Schnitzer, Hans; Santagata, Remo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the much-needed efforts to design sustainable, well-being-oriented economies, based on appropriate energy use in all sectors of a country´s development. Carbon neutrality, energy efficiency and effectiveness, renewable energies, circular economy strategies, environmental consequences of energy use, engagement and empowerment of local communities in decision making, energy and environmental impacts of consumer behavior, and finally science-based approaches towards sustainable production and consumption are the main focus of the research activities described within this book. An effort to go beyond energy scarcity, to promote energy communities, to explore new technologies, and overall, to understand and address the population-lifestyle-energy nexus towards increased and shared well-being is the final result jointly provided by the book authors. All in all, the aim is for the book to be the starting point of a deeper research and understanding of the importance of a radical improvement in energy use in society, beyond considering energy as just a resource in the world market. Circular economy aspects are also investigated, showing the energy saving potential associated with the appropriate design and recovery of material resources.